2013
DOI: 10.47102/annals-acadmedsg.v42n6p285
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Thoracic Biopsy: Evaluating Diagnostic Yield and Complications

Abstract: Introduction: This study retrospectively evaluated CT-guided thoracic biopsies for diagnostic yield, accuracy and complications. Materials and Methods: A retrospective analysis of 384 patients (mean age 62.7 years; male/female = 251/133) who underwent 399 CT-guided thoracic biopsies were performed for evaluating diagnostic yield, accuracy and complications. Correlations between patients age, procedure factors (biopsy-needle size, number of passes, lesion-size, lesion-depth and traversed lung-length) and compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 24 publications
6
15
0
1
Order By: Relevance
“…CTTB had a significantly higher rate of complications compared to RAB (17% vs. 4.4%). The incidence of pneumothorax for CTTB reported in our study is comparable to previously reported complications, ranging from 15% to 52% 6,8,32,33 . The occurrence of pneumothorax post‐RAB in our study was also within ranges from prior publications 24–26 .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…CTTB had a significantly higher rate of complications compared to RAB (17% vs. 4.4%). The incidence of pneumothorax for CTTB reported in our study is comparable to previously reported complications, ranging from 15% to 52% 6,8,32,33 . The occurrence of pneumothorax post‐RAB in our study was also within ranges from prior publications 24–26 .…”
Section: Discussionsupporting
confidence: 89%
“…The most common complications were pneumothorax and hemoptysis. Pneumothorax was considered an adverse effect if it led to admission for observation or chest tube insertion 6 . Hemoptysis was classified according to the Nashville Bleeding Scale, and defined as mild if resolved with suctioning, moderate if required intervention such as wedging of the bronchoscope or instillation of cold saline, and severe if more aggressive measures were necessary and procedure was aborted, including selective intubation for advanced ventilatory support, transfusion or resuscitation 19…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations